Short Hypocotyl in White Light1 Interacts with Elongated Hypocotyl5 (HY5) and Constitutive Photomorphogenic1 (COP1) and Promotes COP1-Mediated Degradation of HY5 during Arabidopsis Seedling Development - Srivastava, Anjil Kumar (Plant Physiol, 2015)
Arabidopsis (Arabidopsis thaliana) Short Hypocotyl in White Light1 (SHW1) encodes a Ser-Arg-Asp-rich protein that acts as a negative regulator of photomorphogenesis. SHW1 and Constitutive Photomorphogenic1 (COP1) genetically interact in an additive manner to suppress photomorphogenesis. Elongated Hypocotyl5 (HY5) is a photomorphogenesis promoting a basic leucine zipper transcription factor that is degraded by COP1 ubiquitin ligase in the darkness. Here, we report the functional interrelation of SHW1 with COP1 and HY5 in Arabidopsis seedling development. The in vitro and in vivo molecular interaction studies show that SHW1 physically interacts with both COP1 and HY5. The genetic studies reveal that SHW1 and HY5 work in an antagonistic manner to regulate photomorphogenic growth. Additional mutation of SHW1 in hy5 mutant background is able to suppress the gravitropic root growth defect of hy5 mutants. This study further reveals that the altered abscisic acid responsiveness of hy5 mutants is modulated by additional loss of SHW1 function. Furthermore, this study shows that SHW1 promotes COP1-mediated degradation of HY5 through enhanced ubiquitylation in the darkness. Collectively, this study highlights a mechanistic view on coordinated regulation of SHW1, COP1, and HY5 in Arabidopsis seedling development.